Isolated Subclinical Hyperthyrotropinemia in Obese Children: Does Levothyroxine (LT4) Improve Weight Reduction during Combined Behavioral Therapy?. (2nd July 2015) - Matusik, Pawel; Gawlik, Aneta; Januszek-Trzciakowska, Aleksandra; Malecka-Tendera, Ewa
Abstract : Objective . The study aim was to analyze whether anthropometrical parameters and TSH values in obese children with isolated subclinical hypothyroidism (IsHT) treated with levothyroxine (LT4) and weight reduction program differ from those managed by dietary and behavior counselling only. Material and Methods . 51 obese children with IsHT, who were treated according to the same weight reduction program, were retrospectively analyzed. They were divided into two groups: Group 1, n = 26, and Group 2, n = 25, without or with LT4 therapy, respectively. Changes in anthropometrical (delta BMI z -score) and hormonal (delta TSH) status were analyzed at the first follow-up visit. Results . In both groups significant decrease of TSH and BMI z -score values were noted. TSH normalized in 80.9% of children from Group 1 versus 90.5% from Group 2, p = NS. Delta BMI z -score was insignificantly higher in Group 1 compared to Group 2. Delta TSH was significantly related to initial TSH level in children treated by lifestyle intervention program only. Conclusions . In obese children with sHT dietary-behavioral management intervention contributed to reduction of body mass index, irrespective of levothyroxine use. This finding suggests that moderately elevated levels of TSH are a consequence rather than cause of overweight and pharmacological treatment should be avoided.